In-time Rice Irrigation Water Management Under Limited Water Supply - Lee, Teang Shui; Haque, Md. Aminul; Mohamed Najim, Mohamed Mujithaba (Universiti Putra Malaysia Press, 2005)
In-time water distribution of canal water to the farmers has been a majorconcern of managers, planners and researchers involved in irrigation. This study analyzed the ways for water distribution and timely water release in a rice growing area during the pre-saturation period and the normal irrigation supply periods. The analyses were carried out using field data collected at the Besut Irrigation Scheme located in the northeastern corner of Peninsular Malaysia in the state of Terengganu. The scheme comprises two sub-schemes, giving a total irrigation area of 5, 164 ha for the overall Besut Irrigation Scheme. Based on field water requirements and available flows at the intake gates, canal simulations were performed and results show that land preparation should not be done continuously unless flow rates are at least 9.00 m3/s and 3.00 m3/s at the Besut Barrage and Angga Barrage respectively. If the respective flow rates fall below these values, then land preparation should be done in two phases. However, when the flow rate is between 5.00 and 5.50 m3/s at the Besut Barrage, land preparation is recommended to be carried out over three phases. During the normal irrigation supply period, flow rates of 6.00 m3/s and 1.75 m3/s for the Besut and Angga Barrage respectively, are to be maintained for the entire irrigation scheme, otherwise selective irrigation or irrigation on a rotational basis has to be enforced. When flow rates are 7.20 - 9.00 m3/s and 1.70 - 3.00 m3/s at the Besut and Angga Barrage respectively, then water should be released two days before the beginning of the pre-saturation period for the filling main and secondary canals. However, water should be released three days before the beginning of the pre-saturation period when flow rates are between 5.00 and 7.00 m3Is at the Besut Barrage. But irrigation water should release 5.00 hours before beginning the normal supply period in order to maintain the in-time irrigation schedule